2021
DOI: 10.3390/v13101906
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ratio Soluble Fms-like Tyrosine Kinase-1/Angiotensin-II (sFlt-1/ANG-II) in Pregnant Women Is Associated with Critical Illness in COVID-19

Abstract: Background: In healthy pregnancies, components of the Renin-Angiotensin system (RAS) are present in the placental villi and contribute to invasion, migration, and angiogenesis. At the same time, soluble fms-like tyrosine kinase 1 (sFlt-1) production is induced after binding of ANG-II to its receptor (AT-1R) in response to hypoxia. As RAS plays an essential role in the pathogenesis of COVID-19, we hypothesized that angiogenic marker (sFlt-1) and RAS components (ANG-II and ACE-2) may be related to adverse outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…In our population, SARS-CoV-2 infection is an independent inflammation factor, added to the pre-existing due to preeclampsia; the significant increases in sFlt-1 concentrations can explain this compared with women with SARS-CoV-2 infection without preeclampsia. Previously, we suggested that interaction between viral spike protein (S) of SARS-CoV-2 and ACE-2 reduces ACE-2 levels in the cell membrane and generates an imbalance of Ang-II/Ang1-7, causing acute hypoxia, which induction and overproduction of sFlt-1, leading to systemic endothelial damage ( 15 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our population, SARS-CoV-2 infection is an independent inflammation factor, added to the pre-existing due to preeclampsia; the significant increases in sFlt-1 concentrations can explain this compared with women with SARS-CoV-2 infection without preeclampsia. Previously, we suggested that interaction between viral spike protein (S) of SARS-CoV-2 and ACE-2 reduces ACE-2 levels in the cell membrane and generates an imbalance of Ang-II/Ang1-7, causing acute hypoxia, which induction and overproduction of sFlt-1, leading to systemic endothelial damage ( 15 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the increased risks of fetal demise and preterm birth, increased incidence of “preeclampsia-like syndrome” has been noted in pregnant patients with SARS-CoV-2 infection ( 2 ). Indeed, evidence suggests that preeclampsia and COVID-19 share similar clinical phenotypes of endothelial dysfunction and may have common pathophysiological mechanisms, especially those involving the renin-angiotensin system (RAS) ( 7072 ). In healthy pregnancies, the RAS components contribute to invasion, migration, and angiogenesis of trophoblast cells ( 73, 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme 2 was also found on trophoblast cells. Pregnant women with severe COVID-19 were found to have elevated maternal plasma concentration of sFlt-1 and a high sFlt-1/PlGF ratio, similar to those developing PE [ 56 ].…”
Section: Introductionmentioning
confidence: 99%